Moss Landing 1. - Unknown:::Creator::::::::::::
The Moss Landing Marine Laboratories (MLML) hosts and administers an interdisciplinary Master of Science Degree in Marine Science for seven California State University (CSU) campuses: East Bay, Fresno, Monterey Bay, Sacramento, San Francisco, San José and Stanislaus. http://info.sjsu.edu/web-dbgen/catalog/departments/MS-section-0.html